Mitochondrial dysfunction in human skeletal muscle biopsies of lipid storage disorder - Debashree, Bandopadhyay; Kumar, Manish; Keshava Prasad, Thottethodi Subrahmanya; Natarajan, Archana; Christopher, Rita; Nalini, Atchayaram; Bindu, Parayil Sankaran; Gayathri, Narayanappa; Srinivas Bharath, Muchukunte Mukunda (Journal of neurochemistry, 2018)
Mitochondria regulate the balance between lipid metabolism and storage in the skeletal muscle. Altered lipid transport, metabolism and storage influence the bioenergetics, redox status and insulin signalling, contributing to cardiac and neurological diseases. Lipid storage disorders (LSDs) are neurological disorders which entail intramuscular lipid accumulation and impaired mitochondrial bioenergetics in the skeletal muscle causing progressive myopathy with muscle weakness. However, the mitochondrial changes including molecular events associated with impaired lipid storage have not been completely understood in the human skeletal muscle. We carried out morphological and biochemical analysis of mitochondrial function in muscle biopsies of human subjects with LSDs (n = 7), compared to controls (n = 10). Routine histology, enzyme histochemistry and ultrastructural analysis indicated altered muscle cell morphology and mitochondrial structure. Protein profiling of the muscle mitochondria from LSD samples (n = 5) (vs. control, n = 5) by high‐throughput mass spectrometric analysis revealed that impaired metabolic processes could contribute to mitochondrial dysfunction and ensuing myopathy in LSDs. We propose that impaired fatty acid and respiratory metabolism along with increased membrane permeability, elevated lipolysis and altered cristae entail mitochondrial dysfunction in LSDs. Some of these mechanisms were unique to LSD apart from others that were common to dystrophic and inflammatory muscle pathologies. Many differentially regulated mitochondrial proteins in LSD are linked with other human diseases, indicating that mitochondrial protection via targeted drugs could be a treatment modality in LSD and related metabolic diseases. Cover Image for this Issue: doi: 10.1111/jnc.14177. We carried out morphological and biochemical analysis of mitochondrial function in muscle biopsies of patients with lipid storage diseases (LSDs). LSD muscle displayed altered cell morphology and mitochondrial structure. Mitochondrial proteomics of LSD muscle revealed that impaired fatty acid metabolism, Krebs cycle and oxidative phosphorylation, etc., along with increased mitochondrial permeability and elevated lipolysis entail mitochondrial dysfunction and ensuing myopathy. Cover Image for this Issue: doi: 10.1111/jnc.14177.